The Kibbutz : a new way of life - Leon, Dan, 1925- (Commonwealth and international library., 1969)
The Kibbutz: A New Way of Life provides an introduction to the Kibbutz Artzi Hashomer Hatzair, which is the largest of the four national federations of kibbutzim or national settlements in Israel. This book presents the problems and the achievements of the kibbutz. Organized into three parts, this book begins with an overview of the development of the kibbutz movement, which is considered an integral part of the broad social and national struggles that accompany every national liberation movement. This text then examines the influences that motivated the foundation of the first kibbutz groups.